Global Swimways for the conservation of migratory freshwater fishes. Issue 10 (4th August 2022) - Worthington, Thomas A; van Soesbergen, Arnout; Berkhuysen, Arjan; Brink, Kerry; Royte, Joshua; Thieme, Michele; Wanningen, Herman; Darwall, William
Abstract: Anthropogenic activities have severely degraded the ecological integrity of global freshwater systems. Migratory freshwater fishes are especially threatened by the cumulative effects of multiple stressors and fragmentation, particularly those that impede access to critical habitats. To stimulate the conservation and protection of these species, we propose a "Global Swimways" program to identify rivers that support the migration routes of biologically and/or socioeconomically important freshwater fishes. We test the utility of the International Union for Conservation of Nature Red List data to support the identification of Global Swimways and present case study regions containing rivers with either high species richness (west‐central Africa and Southeast Asia), high numbers of threatened species (Eastern Europe and Central Asia), or multiple endemic species (the Rift Valley lakes in East Africa). We hope the Global Swimways program will provide metrics that can be used to identify rivers requiring increased protection or restoration, track trends, and stimulate the greater inclusion of migratory freshwater fishes in global policy mechanisms. Front Ecol Environ 2022;